Body art as branded labour: At the intersection of employee selection and relationship marketing. (September 2017) - Timming, Andrew R
Using mixed methods, this article examines the role of body art as a form of branded labour in customer-facing jobs. It brings together employee selection and relationship marketing into one framework, and uniquely conceptualizes body art as an asset in the labour market, rather than the traditional liability. In Study 1, 192 respondents with management experience participated in an online laboratory experiment in which they were asked to rate photographs of tattooed and non-tattooed job applicants in two hypothetical organizations: a fine dining restaurant and a popular nightclub. In Study 2, 20 in-depth, qualitative interviews were carried out with managers, tattooed front-line employees and potential consumers in two real-world service sector firms. The results show how body art can be strategically used to positively convey the brand of organizations, primarily those targeting a younger, 'edgier' demographic of customer.